The Study of Plasmonic Chip of Nata de Sago-green Silver Nanoparticles for Detection of Blood Glucose - Abdul Haris Haris Watoni; La Ode A. Nur Ramadhan; Evy Nuryah Adha; Robby Sudarman (Chimica et Natura Acta, 2023)
The innovation of rapid blood glucose level detectors using chemical sensors still needs to be carried out continuously. Nata de sago has good potential as a safe sensor chip for blood glucose detection. To increase the detection speed, this sensor chip can be composited with silver nanoparticles (AgNPs)-bidara leaf extract which has plasmonic properties when interacting with visible radiation. The principle of blood glucose detection with the nata de sago-AgNPs-bidara leaf extract composite chip is based on van der Waals interactions between the functional groups in nata de sago and the hydroxyl groups in glucose compounds which are strengthened by the plasmonic nature of AgNPs.This study aims to synthesize and characterize nata de sago cellulose composite films embedded with silver nanoparticles as blood sugar detection sensor chips. Silver nanoparticles (AgNPs) were synthesized from AgNO3 precursors using bioreductors and capping agents of bidara leaf extract (Ziziphus mauritiana L.) with various volume ratios of precursor to bioreductor 1:1, 1:2, 1:3, 1:4, 1:5 and 1:6. The nata de sago-AgNPs-bidara leaf extract composite was made by soaking the nata de sago film in a suspension of AgNPs-bidara leaf extract for 1 hour until the film turned yellow. The film was then dried for 24 hours at room temperature to obtain a cuvette type plasmonic film which was ready for characterization and validation.FTIR analysis showed the formation of silver particles based on vibrational spectra changes of functional groups of bioreductor compounds at wave numbers 3423 cm-1, 2924 cm-1, 1641 cm-1 and 1056 cm-1. Morphological analysis using a digital microscope showed that the AgNPs were not uniformly spherical. Particle size analysis using a UV-Vis spectrophotometer showed that the AgNPs formed had an estimated diameter of 32.231 – 82.261 nm. Composite film of nata de sago-AgNPs-bidara leaf extract can be used as a blood glucose sensor chip by UV-Vis spectrophotometry with LOD = 30.814 mg/dL, LOQ = 50.814, %RSD = 5.015, and %R 90.68. The values of these parameters indicate that the sensor chip has good precision (%RSD) and accuracy (%R).